Repurposable Hardware in Smart Photonic Components. Issue 1 (May 2021) - Anderson, Mike; Philips, Ian; Callan, Paul; Forysiak, Wladek
Abstract: Key to the development of cost effective integrated components is low cost, low power circuitry capable of being repurposed from providing manufacturing based functions, such as characterisation and calibration, to operational control functions. Although these individual functions are well known, efficient and low cost implementations are required to enable competitive module pricing. In the case of an optical Mach Zehnder Modulator (MZM), bias currents require complex control functions, for example based around digitally synthesized sinusoidal pilot tones and harmonic detection via filters [1][2]. Control methods making use of calibrated laboratory equipment have been proposed [2], whereas here we consider the practical adoption of these methods with low cost and low power components which could be readily integrated into an optical module. In particular we investigate the behaviour and capabilities required for automatic digital bias control functionality implemented in a small gate count, low cost Field Programmable Gate Array (FPGA) when used in conjunction with a MZM. We assess the suitability of highly efficient implementations of DSP functions within the bias controller, such as digital filters, for example investigating the use of a computationally efficient algorithm for computing a single component of a discrete Fourier transform [3], and demonstrate the viability of using low cost digital hardware to implement a circuit capable of monitoring the MZM transfer function. The concept of creating cost effective, repurposable hardware is crucial for implementation and inclusion in optical devices deployed in communications networks and beyond.